Computer aided classification of diagnostic terms in spanish. Issue 6 (15th April 2015) - Pérez, Alicia; Gojenola, Koldo; Casillas, Arantza; Oronoz, Maite; Díaz de Ilarraza, Arantza
Highlights Framework to classify Medical Records by their diagnostic terms. Resources: ICD catalogue, SNOMED ontology, Medical Records and synonym dictionaries. Finite-State Transducers efficiently implement soft-matching operations. An F1-measure of 91.2 was achieved on a test-set of 2850 diagnostic terms.